Violeta Luna: Dramaturgia y performatividad de la desaparición - Martin Sanchez, Maria Isabel (Latin American Theatre Review, 2022)
Requiem #3: Body Graves (2019) is part of the Requiem project, a series of interventions in which Violeta Luna explores the representation of violence as a ritual and uses her body as a territory for political-social dialogue. This participatory performance draws attention to those who are buried in mass graves in Mexico and seeks to rescue their existence from oblivion, while questioning institutional impunity and involving the viewer in the search efforts. In a context in which the task of locating the remains of loved ones falls on civil society, the piece highlights how the disappeared and their families are victims of the ineffectiveness of the “narco-machine” that has become the Mexican State (Reguillo). Therefore, in my essay I examine Requiem #3 as a performative work that embodies disappearance and in which ritual, visual, and auditory aspects converge. In the piece, sonic dramaturgy, deconstructed objects, and theatrical practices are emphasized to work within the effects of absence, search, and mourning. The theoretical framework that I use is interdisciplinary, emphasizing visual, sound, and performance studies. Beyond that, I am focusing on the interpretations of necropolitics (Mbembe), gore capitalism (Valencia) and necrotheatre (Diéguez Caballero). Finally, I address how music and sounds, along with body movements and acting objects (Bennett), transforms the stage into an altar that highlights the (un)burial of memory.